SPINK5 is a Prognostic Biomarker Associated With the Progression and Prognosis of Laryngeal Squamous Cell Carcinoma Identified by Weighted Gene Co-Expression Network Analysis. (February 2022) - Liu, Jian; Zhao, Jing; Xu, Jiaran; Sun, Qing; Qin, Xuemei; Chen, Guohui; Gao, Tianle; Bai, Guangping; Guo, Zhiqiang
Laryngeal squamous cell carcinoma (LSCC) is one of the most common types of head and neck squamous cell carcinomas (HNSCC) and is the second most prevalent malignancy occurring in the head and neck or respiratory tract, with a high incidence and mortality rate. Survival is limited for patients with LSCC. To identify more biomarkers associated with the prognosis of patients with LSCC, using bioinformatics analysis, this study used The Cancer Genome Atlas (TCGA) LSCC dataset and gene expression profiles of GSE59102 from the Gene Expression Omnibus (GEO). Eighty-one differentially co-expressed genes were identified by weighted gene co-expression network analysis (WGCNA). Next, 10 hub genes (PPL, KRT78, CRNN, PTK7, SCEL, AGRN, SPINK5, AIF1L, EMP1, and PPP1R3C) were screened from a protein-protein interaction (PPI) network. Based on survival analysis, SPINK5 was significantly correlated with survival time in LSCC patients. After verification in the TCGA and HPA databases, SPINK5 was selected as a prognostic biomarker. Finally, the GSEA results showed that downregulation of SPINK5 gene expression may promote tumorigenesis and the development of cancers by the "BASAL CELL CARCINOMA" pathway, and it has been implicated in disrupting DNA damage and repair pathways. Collectively, SPINK5 may serve as a potential prognostic biomarker in LSCC.